Non-cooperative decision: Making and measures of household surplus - Ian J. Bateman; Alistair Munro (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2003)
Given the evidence against the unitary model of the household, there is a need to understand the predictions of alternative household models within the context of valuation. This paper derives the relationship between household and individual willingness to pay (WTP) for the non-cooperative model of the household. We stress the dependence of WTP on a) the conjectures held by respondents about the behaviour of other members of the household and b) on whether all the members of the household make contributions to household public goods. The results suggest that the relationship between individual WTP and household WTP may be a complex one and that identifying gender-specific environmental preferences may not be possible within standard stated preference exercises.
Keywords: 330; consumer surplus; Contingent valuation; gender; household behaviour; Nash; Stated preference; Willingness to pay; Konsumentenverhalten; Privater Haushalt; Haushaltsökonomik